A Critical Analysis of a Wireless Power Transmission (WPT) with an Improvement Method for a Non-Radiative WPT - Muhammad Ali; Nurulazlina Ramli; Hermawan Nugroho (IAES Indonesian Section, 2020)
This paper describes the analysis of the wireless power transmission including recent progresses in non-radiative wireless power transmission (WPT) and the improvement methods. Generally, WPT transmitter side consists of a DC supply voltage source, inverter/power amplifier, transmitter impedance matching device (IMD), source resonator and primary coil. The WPT receiver meanwhile consists of the secondary coil, device resonator, receiver IMD, rectifier and load. In order to achieve an efficient WPT, the WPT transmitter must transmit energy with minimum loss at the receiver side. This setup can be achieved by employing the power amplifier (PA). In this paper, the power amplifier in wireless power transmission for portable devices was designed. A Class E power amplifier was proposed and designed to improve the WPT transmitter side. The effects of zero voltage and zero derivative voltage switching on PA with optimization method was also discussed.